Efektivitas Penegakan Hukum Tindak Pidana Penadahan Laptop di Kota Makassar - Jumaris, Jumaris; Husen, La Ode; Hambali, Azwad Rachmat (SIGn Jurnal Hukum, 2025)
The persistent criminal offense of receiving stolen laptops poses a significant challenge to the criminal justice system in Indonesia. This study aims to analyze the effectiveness of law enforcement against this offence in Makassar City and comprehensively identify and analyze the factors that influence it. The method employed is empirical legal research conducted in Makassar City, involving primary data collection through administering questionnaires to 25 respondents and in-depth interviews with key informants, supplemented by secondary data from a documentary study. Data analysis integrates descriptive quantitative and interpretive qualitative approaches guided by the theoretical framework of legal effectiveness. The primary results of the study convergently indicate that the effectiveness of law enforcement regarding the criminal offense of receiving stolen laptops in Makassar City is generally assessed as less effective, as reflected in the majority perception of respondents and qualitative indicators such as the persistence of perpetrators and the weak deterrent effect of criminal sanctions. Factor analysis identifies several significant determinants contributing to this condition, including limited preventive capacity within the legal structure, low public legal awareness and caution in second-hand goods transactions, the presence of substantial operational constraints in the investigation process, and the dynamics of cooperation between perpetrators of theft and receivers which strengthen criminal resilience. It is concluded that the low effectiveness of law enforcement is the result of the complex interaction of these structural, cultural, operational, and criminal environment factors.